3(x+2)-4=x+2x+2

Simple and best practice solution for 3(x+2)-4=x+2x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)-4=x+2x+2 equation:


Simplifying
3(x + 2) + -4 = x + 2x + 2

Reorder the terms:
3(2 + x) + -4 = x + 2x + 2
(2 * 3 + x * 3) + -4 = x + 2x + 2
(6 + 3x) + -4 = x + 2x + 2

Reorder the terms:
6 + -4 + 3x = x + 2x + 2

Combine like terms: 6 + -4 = 2
2 + 3x = x + 2x + 2

Reorder the terms:
2 + 3x = 2 + x + 2x

Combine like terms: x + 2x = 3x
2 + 3x = 2 + 3x

Add '-2' to each side of the equation.
2 + -2 + 3x = 2 + -2 + 3x

Combine like terms: 2 + -2 = 0
0 + 3x = 2 + -2 + 3x
3x = 2 + -2 + 3x

Combine like terms: 2 + -2 = 0
3x = 0 + 3x
3x = 3x

Add '-3x' to each side of the equation.
3x + -3x = 3x + -3x

Combine like terms: 3x + -3x = 0
0 = 3x + -3x

Combine like terms: 3x + -3x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| F(x)=3x^2+7x-6 | | x^3=578 | | 7x+y=-10x+6 | | 56/x-4 | | 4k-7k=(-20)-1 | | 7.5/50=c | | 7x-14=3x-4 | | 0.7x-1.4=0.3 | | x(3x+14)=-8 | | 1250+92*p=7000 | | 3(3)-2(1)= | | 5+14.50p=64 | | (w)(2w+8)2=26.25 | | (10-3)4+6= | | 4x+21y=229 | | 0.512*28=u | | 7.50+1.35t=12.90 | | u=p/n | | 68/x-4 | | y=3/4x-1/2 | | 2x+3y=6.50 | | y=6x+289 | | 3.14*81=254.34 | | .2=x-2.76 | | 80x^2=-5 | | (2w+8)2=26.25 | | 3(5)-2(4)= | | 5(u-1)-(u-2)=10-(2u+1) | | 4(-7)+3(-8)= | | 9(d+7a)= | | x*y=13599273702913 | | 2(7)+3(4)= |

Equations solver categories